2022
DOI: 10.1101/2022.01.17.22269284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmaceutical Payments to Japanese Certificated Hematologists: A Retrospective Analysis of Personal Payments from Pharmaceutical Companies between 2016 and 2019

Abstract: Background: A growing and significant financial relationship exist between physicians and pharmaceutical companies. However, little is known about the characteristics and trends of personal payments from pharmaceutical companies to hematologists. This study was aimed to evaluate the financial relationship between hematology specialists and pharmaceutical companies in Japan between 2016 and 2019. Methods: Descriptive analyses were performed to evaluate personal payments from 92 major pharmaceutical companies to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Although the prevalence of specialists with payments were similar to the previous findings, ranging from 62.0% among hematologists to 70.6% among medical oncologists [3,4,15,23], payment values per specialist among the infectious disease specialists ($3,183 in median four-year combined payments and $1,430-$1,720 in median single-year payments) were higher than all of the available evidence among pediatric oncologists ($2,961 in average) [23], pulmonologists ($2,210 in median) [3], hematologists ($2,471 in median) [23], and medical oncologists ($1,103 in one-year median) [15] in Japan. Overall, compared to the previous studies, Japanese infectious disease specialists have higher financial relationships with pharmaceutical companies.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Although the prevalence of specialists with payments were similar to the previous findings, ranging from 62.0% among hematologists to 70.6% among medical oncologists [3,4,15,23], payment values per specialist among the infectious disease specialists ($3,183 in median four-year combined payments and $1,430-$1,720 in median single-year payments) were higher than all of the available evidence among pediatric oncologists ($2,961 in average) [23], pulmonologists ($2,210 in median) [3], hematologists ($2,471 in median) [23], and medical oncologists ($1,103 in one-year median) [15] in Japan. Overall, compared to the previous studies, Japanese infectious disease specialists have higher financial relationships with pharmaceutical companies.…”
Section: Discussionsupporting
confidence: 87%
“…Kusumi et al found that the pharmaceutical companies increasingly prioritized the payments to hematologists in Japan, with a 11.2% annual increase in payments per specialist. [4] Also, similar trends were observed by Murayama et al among Japanese pulmonologists, with 7.8% annual increase in payments. [3] Our finding was different from these studies, indicating that the financial relationships among infectious disease specialists and pharmaceutical companies did not decline nor increase, but remained stable for the last four years.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations